Kesejahteraan Sosial Masyarakat Pengrajin Sapu Lidi Sawit Di Era Pandemi Covid-19 (Studi Kasus Kelurahan Tanjung Langkat, Kecamatan Salapian, Kabupaten Langkat) - Nicky Very Bangun (Universitas Muhammadiyah Sumatera Utara, 2023)
This study discusses the social welfare of the palm oil broom craftsman in the era of the covid-19 pandemic in Tanjung Langkat Village, Salapian District, Langkat Regency. The purpose of this study is to describe the differences in life between before and during the Covid-19 pandemic felt by the community of palm oil broom craftsmen in Tanjung Langkat Village, Salapian District, Langkat Regency. This study uses descriptive qualitative research methods with data collection techniques through observation, interviews, and literature studies and analyzes them by collecting data, reducing data, presenting data, and drawing conclusions (verification). The results of this study indicate that the life of the palm broom craftsman in Tanjung Langkat Village, Salapian District, Langkat Regency during the COVID-19 pandemic can be said to have changed. This is viewed from the indicators of community welfare, including the family economy, education and health.